Proyecto de factibilidad para la creación de una empresa de Asesoría Nutricional y Estética Integral en la ciudad de Cayambe, provincia de Pichinch - Carvajal Carrera, Katia Elizabeth (2014)
The project is aimed at people between 15 and 65 years of age, social class and upper middle, in urban parishes of the city of Cayambe. The target market for this proposed project is 24,408 people including men and women. A pilot survey to 50 people where the probability of consumption is 64% was applied, and a sample of 349 surveys study based on the proposed target market was obtained. The potential demand 186,721 visits per year. The price has been set for the services offered are: $ 40 for face, body and $ 35 to $ 24 for nutritional counseling.